18.88%-efficient multi-crystalline silicon solar cells by combining Cu-catalyzed chemical etching and post-treatment process. (15th July 2018) - Wang, Ping; Xiao, Shaoqing; Jia, Rui; Sun, Hengchao; Dai, Xiaowan; Su, Guoyu; Tao, Ke
Graphical abstract: A combination of Cu-MCCE method and a HF/HNO3 /H3 PO4 post-processing treatment process is used to decorate the surface morphology of Si textures, which is demonstrated to be helpful in reducing surface recombination and improving the cell performance. Highlights: Two-step Cu-MCCE etching method was utilized for the texture of mc-Si solar cells. A HF/HNO3 /H3 PO4 post-treatment was adopted to decorate such Si textures. The post-treatment is helpful in reducing surface recombination and improving cell performance. The highest efficiency of such two-step Cu-MCCE mc-Si solar cells reaches 18.88%. The mechanism can be attributed to both less surface recombination and high compatibility. Abstract: Mass production of diamond-wire-sawn (DWS) multi-crystalline silicon (mc-Si) solar cells reached a significant point of maturity through utilization of metal-catalyzed chemical etching (MCCE). However, the reported studies always focus on how to optimize the MCCE process but there are few studies concentrating on the post-treatment techniques to improve the cell efficiency. In this paper, we use a combination of Cu-MCCE method and a HF/HNO3 /H3 PO4 post-processing treatment process to decorate the surface of Si textures for the first time. The submicron polygonal chamfered cone structure produced by the post-processing treatment is demonstrated to be helpful in reducing surface recombination and improving the cell performance in terms of surface morphology, reflectivity, internal quantum efficiency (IQE) and external quantum efficiency (EQE) measurements as well as Electroluminescence (EL) spectra characterizations. The highest efficiency of Cu-MCCE mc-Si solar cells subjected to such post-processing treatment process is 18.88% with short circuit current (Isc), open circuit voltage (Voc) and fill factor (FF) of 36.67 mA/cm 2, 638.6 mV and 80.64%, respectively, in great contrast to that (16.81%) of Cu-MCCE mc-Si solar cells without any post treatment. The post-treatment process is, therefore, of great potential for the Si photovoltaic industry, especially for the Cu-MCCE mc-Si solar cells.